Estudio comparativo de ingresos y gastos de los años 2017 y 2018 de la empresa CAMPUNPEL S.A camarones punta pelada - Monserrate Ramos, Aldo Alejandro (2020)
The subject of this research work is "Comparative Study of Income and Expenses of the years 2017 and 2018 of the company Campunpel S.A Camarones Punta Pelada", which is dedicated to the exploitation of shrimp larvae hatcheries and sale of the same. The company reflects losses in its financial statements for the periods 2017 and 2018, in the statement of comprehensive income it is observed how the value of its ordinary income is less than the value of its costs and expenses, with the application of a horizontal analysis, graphs in excel and ratio analysis, a comparative study was carried out to observe the variations existing from one year to the next in each item immersed in income, costs and expenses. The work carried out is carried out within the framework of the Accounting Information Management sub-line of the Accounting and Auditing Engineering degree, since a comparative study of the entity's income and expenses in fiscal periods 2017 is carried out. and 2018. The aspects that cause the level of income to be low compared to costs and expenses are identified, which generates little liquidity and profitability within the company.